Adaptación colombiana de las guías para el uso de neuroestimulación espinal en el manejo del dolor crónico e isquémico (2016)
ABSTRACT: Introduction: Management of chronic pain by conventional means is usually insufficient, but the enhanced knowledge of the neurobiology of pain has led to the development of new treatments like spinal neurostimulation, with optimal short- and long-term results. Objectives: To integrate and update clinical practice guidelines on the effectiveness and safety of spinal neurostimulation in the management of chronic pain. Materials and methods: Search of practice guidelines, systematic reviews and clinical trials in the main databases (Cochrane, EMBASE, LILACS and MEDLINE), and assessment of their quality and level of evidence in order to propose recommendations for the management of chronic painful syndromes and cardiac and lower-limb ischemia. Results: Suficient evidence was found to support the use of spinal neurostimulation for pain relief in cases of persistent pain after back surgery and also for complex regional pain syndrome. Growing evidence was found for the use of spinal neurostimulation in refractory angina pectoris and in painful ischemic lower limbs. Conclusions: Neurostimulation is a minimally invasive technique useful for the management of persistent pain after back surgery and for complex regional pain syndrome.